2004
DOI: 10.1370/afm.244
|View full text |Cite
|
Sign up to set email alerts
|

Improving Test Ordering in Primary Care: The Added Value of a Small-Group Quality Improvement Strategy Compared With Classic Feedback Only

Abstract: PURPOSE We wanted to evaluate the added value of small peer-group quality improvement meetings compared with simple feedback as a strategy to improve test-ordering behavior. Numbers of tests ordered by primary care physicians are increasing, and many of these tests seem to be unnecessary according to established, evidence-based guidelines. METHODSWe enrolled 194 primary care physicians from 27 local primary care practice groups in 5 health care regions (5 diagnostic centers). The study was a cluster randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 25 publications
0
53
0
1
Order By: Relevance
“…improvement, 42 have been shown to effectively reduce demand. However, such interventions can be costly, and in some cases the savings made may be less than the programme cost.…”
Section: Competing Interestsmentioning
confidence: 99%
“…improvement, 42 have been shown to effectively reduce demand. However, such interventions can be costly, and in some cases the savings made may be less than the programme cost.…”
Section: Competing Interestsmentioning
confidence: 99%
“…Many attempts have been made with the aim of improving the appropriateness of test requesting behavior, as well as reducing the testing volume (13)(14)(15). Continuous education of medical doctors has been demonstrated as an effective means for decreasing redundant tests ordering in the hospital setting (16) as well as by practicing community physicians (17).…”
mentioning
confidence: 99%
“…Therefore, we should focus our attention directly on improving physical and mental functioning and improving quality of life." 12,9 [For feedback] "[t]o be infl uential, a number of prerequisites have to be met.…" 13,14 "A successful, but single intervention generally does not last a long time." 13,14 "Theory: the challenge for translating evidence into practice."…”
mentioning
confidence: 99%
“…12,9 [For feedback] "[t]o be infl uential, a number of prerequisites have to be met.…" 13,14 "A successful, but single intervention generally does not last a long time." 13,14 "Theory: the challenge for translating evidence into practice." 15,14 "A Dutch study in primary care found that diagnostic testing, labeled as superfl uous by a panel of experts, had no negative effect on health status and that medical consumption was not higher in patients that underwent excessive testing."…”
mentioning
confidence: 99%
See 1 more Smart Citation